Applications of non-parametric testing in a chemical industry - Oliveira, Alexandra Cristina de; Barros, Jose Glenio Medeiros de; Almeida, Maria da Gloria Diniz de; Carvalho, Cleginaldo Pereira de [UNESP]; Sampaio, Nilo Antonio de Souza (Sindicato Secretarias Estado Sao Paulo, 2023)
This study aimed to identify research gaps on the topic Non-Parametric Statistical Tests, specifically showing an application of the Mann-Whitney Test. To achieve this goal, an application of this test was performed on data from a chemical industry in the South Fluminense region. It is noteworthy that the confidentiality of the data was prioritized, for the sake of the company's interest.
Keywords: Statistical Software; Non-Parametric Statistical Tests; Parametric Statistical Tests; Mann-Whitney Test